In vitro antibacterial activities and composition of Carica papaya cv. Sekaki/ Hong Kong peel extracts - A. S., Muhamad S.; B., Jamilah; A. R., Russly; A., Faridah (Faculty of Food Science & Technology, UPM, 2017)
Ten solvents were used to extract phytochemicals from the peel of Carica papaya cv. Sekaki/Hong Kong to determine their antibacterial activities. Moderate to clear inhibition on Corynebacterium diphtheriae, Streptococcus pneumoniae, Bacillus subtilis and Clostridium perfringens were obtained from the disk diffusion test out of fourteen pathogens tested. Petroleum ether extract, the most potent extract, showed moderate inhibition towards C. diphtheriae and S. pneumoniae at MIC of 5.63 mg/mL and 1.40 mg/mL. Polar solvents gave higher yield, total phenolic and total flavonoid contents than nonpolar solvents. Extract yields were 10.9 to 84.1 mg/g in polar solvents and 3.9 to 20.3 mg/g in non-polar solvents. Twenty eight compounds were identified in petroleum extracts through GC/MS analysis. Among the compounds identified were fatty acids, esters, alkane, tocopherols and sterols. 9,12,15-octadecatrienoic acid was the most abundant compound.